Spatially: resolved heterogeneous dynamics in a strong colloidal gel. (20th May 2015) - Buzzaccaro, Stefano; Alaimo, Matteo David; Secchi, Eleonora; Piazza, Roberto
Abstract We re-examine the classical problem of irreversible colloid aggregation, showing that the application of Digital Fourier Imaging (DFI), a class of optical correlation methods that combine the power of light scattering and imaging, allows one to pick out novel useful evidence concerning the restructuring processes taking place in a strong colloidal gel. In particular, the spatially-resolved displacement fields provided by DFI strongly suggest that the temporally-intermittent local rearrangements taking place in the course of gel ageing are characterized by very long-ranged spatial correlations.